1985
DOI: 10.1136/bmj.290.6470.746
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of systemic Candida albicans in intensive care unit caused by cross infection.

Abstract: The first documented outbreak of systemic candidosis shown to be due to cross infection with a particular strain of Candida albicans is reported. Over nine months in an intensive care unit 13 patients developed definite and one probable systemic candidosis. Twenty five further patients had superficial candidal infections. The strain that caused the outbreak (serotype A, morphotype

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(68 citation statements)
references
References 20 publications
1
66
1
Order By: Relevance
“…In the present study none of the samples from NICU or from hands of health care workers were positive for Candida as also reported by Baley et al 4 and Burnie et al 6 In contrast, a high yeast carriage by health care personnel of a tertiary care hospital in Chandigarh was considered to be the possible reason for high yeast colonization among preterms admitted in the NICU. The frequency of colonization observed in our study was close to that reported by Baley et male sex, prolonged DROM, administration of steroids and 5.…”
Section: Discussionsupporting
confidence: 40%
“…In the present study none of the samples from NICU or from hands of health care workers were positive for Candida as also reported by Baley et al 4 and Burnie et al 6 In contrast, a high yeast carriage by health care personnel of a tertiary care hospital in Chandigarh was considered to be the possible reason for high yeast colonization among preterms admitted in the NICU. The frequency of colonization observed in our study was close to that reported by Baley et male sex, prolonged DROM, administration of steroids and 5.…”
Section: Discussionsupporting
confidence: 40%
“…The predominant profile was given by the hospital outbreak strains which were all of the same biotype (Burnie et al 1985). Significantly, these assimilations were performed at their varying times of initial clinical isolation by different people and were identical; with the results of assimilations at 37 and 30°C, these profiles have been shown to be both consistent and reproducible, provided uniform methodology is performed.…”
Section: Discussionmentioning
confidence: 74%
“…These isolates were considered indistinguishable upon biotyping by the method of . The cross-infection outbreak and biotyping are described elsewhere (Burnie et al 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Lee et al (1986) characterized 190 C. albicans strains isolated from 142 pacients in the London Hospital based on total protein content and Western blot analysis. This technique used an antiserum produced in rabbbits against a prenssate of C. albicans NCTC 3153 serotype A, and was more sensitive than the procedure previously used with these same strains serotyped, morphotyped, and biotyped during an outbreak of systemic C. albicans which has been described Burnie et al (1985).…”
Section: Introductionmentioning
confidence: 99%